Upaya Peningkatan Mutu Pendidikan melalui Optimalisasi Program Pelatihan dan Pembiasaan di SMP Negeri 9 Bandung - Anatasya Jelita Putri Dirgantara; Maula Diah Liani; Vyanara Aulyadisha; Aghnia I’lmi Diniyati (Lembaga Pengembangan Kinerja Dosen, 2025)
Habituation programs and teacher training are efforts to improve the quality of education in building a school environment with character. Improving the quality of education continues to experience changes and developments along with advances in time and technology. This research analyzes efforts to improve the quality of education at SMP Negeri 9 Bandung through optimizing teacher training programs and student habituation. The method used in this research is a descriptive qualitative approach through interviews and observations. This research aims to describe a strategy, implementation and also the results of a program to improve the quality of education at the junior high school level. The teacher training program is designed to improve teachers' technical competence and soft skills, especially in the use of learning technology. This aims to improve the quality of teaching and adapt to technological developments. Meanwhile, the student habituation program focuses on character building, such as literacy, environmental cleanliness, sports and religious activities, to foster discipline and a sense of caring. Schools also utilize technology in learning, such as using projectors and smartphones to support computer-based interactions and assessments. Apart from that, collaboration with the community and parents of students is also very important in supporting educational activities, including providing a budget for the Strengthening Pancasila Student Profile (P5) Project activities. This holistic approach creates a conducive and quality learning environment, which has a positive impact on educational outcomes and the achievement of national education goals.